Quality of life of mothers of children with Autistic Spectrum Disorder (Research, Society and Development, 2019)
Autistic Spectrum Disorder (ASD) has important consequences on social interaction and the possibility of acquiring autonomy, which generates permanent dependence on their families. Culturally, in our society, it is mothers who assume this role. The aim of the study was to evaluate the quality of life of mothers who have children diagnosed with ASD and correlate it with socio-demographic, obstetric and child data. Quantitative, descriptive and cross-sectional survey of 17 mothers of children with ASD attending a support group from a Specialized Rehabilitation Center (SRC). Data collection was performed in two ways: application of the WHOQOL-bref instrument and collection of socio-demographic, obstetric and child variables, through the medical records of the service. The average quality of life score of the mothers was 64.47. There was a significant correlation between maternal education and physical domain and between the variable “children's ability to interact with other children” and the social domain of mothers.  The variable “number of children” showed a significant negative correlation with the environment domain. Therefore, when analyzing the average quality of life score of these mothers, it is concluded that it is necessary to observe this population more carefully.